Paresthesia of the inferior alveolar nerve caused by periapical pathology: case report - F. R. Ismailov; Z. S. Khabadze (LLC "Endo Press", 2022)
Paresthesia in the chin area may not always be caused by a neurological condition. Sometimes persistent and prolonged treatment of the trigeminal nerve for neuralgia, does not have a positive result. One cause of mandibular numbness may be caused by compression on the mandibular canal by an odontogenic cyst.Aim. To demonstrate the clinical symptomatology and radiological signs of mandibular nerve damage in a 48-year-old patient who underwent re-treatment of the lower left seventh tooth in 2 visits with long-term clinical and radiological follow-up.